PENGARUH KEJELASAN SASARAN ANGGARAN, KETEPATAN ANGGARAN, SISTEM PENGENDALIAN INTERN PEMERINTAH DAN KOMUNIKASI INTERNAL TERHADAP KINERJA INSTANSI PEMERINTAH KABUPATEN KOLAKA - Manurung, Novelty NKP; Dali, Nasrullah; Nurdin, Emilia (Pascasarjana Universitas Halu Oleo, 2019)
This Study Aims To Find Out And Analyze The Influence Of The Clarity Of The Budget Target, The Government's Internal Control System And Internal Communication On The Performance Of The Kolaka Regency Government. The Type Of Research Used In This Study Is Causality Research With A Quantitative Approach. The Samples In This Study Were Head Of Service, Head Of Sub-District, Head Of Planning Sub-Department, Head Of Subdivision Of Finance, And Head Of Subdivision Of Planning And Finance As Many As 102 Peoples. The Results Of This Study Indicate That Partially There Is The Influence Of The Clarity Of The Budget Target On The Performance Of The Kolaka Regency Government Agency With A Value Of Tcount (3,454)>Ttable (1,66) And Sig Value. (0,001) <Î‘ (0.05), There Is No Influence Of The Government's Internal Control System On The Performance Of The Kolaka Regency Government Agency With A Value Of Tcount (0.498)<Ttable (1.66) And Sig Value. (0.620) >Î‘ (0.05), And There Is An Influence Of Internal Communication On The Performance Of The Kolaka Regency Government AgencyÂ With A Value Of Tcount (7.690)>Ttable (1.66) And Sig Value. (0.000) <Î‘ (0.05). The Amount Of The Coefficient Of Determination Is 0.475. This Means That The Contribution Of Independent Variables (Clarity Of Budget Target, Budget Accuracy, The Government's Internal Control System, And Internal Communication) To The Performance Of Kolaka Regency Government Intention Is 0.764 Or 76.4%, While The Remaining 23.6% Is The Influence Of Other Variables Who Were Not Included In This Study.Â Â Keywords: Budget Clarity, Budget Accuracy, The Government's Internal Control System, Internal Communication, Performance